Relational Islamization and Divergent Trajectories in Indonesia and Malaysia - Mahin Anas Romadona; Irfan Musonif; Rohman Hakim; Kholid Mawardi (Values: Jurnal Kajian Islam Multidisiplin, 2026)
This study aims to reconstruct the understanding of Islamization in Southeast Asia through a comparative analysis of Indonesia and Malaysia, emphasizing the relationship between origin narratives and the dynamics of Islamic development. The research employs a qualitative library-based approach using thematic synthesis of Scopus-indexed academic literature. The findings demonstrate that Islamization cannot be adequately explained as a linear or diffusionist process; rather, it constitutes a relational configuration shaped by the interaction of origin narratives, transregional networks, cultural mechanisms, and institutional structures. The study further reveals that the plurality of origin narratives functions as an epistemological foundation that influences the trajectory of Islamization in different contexts. Comparatively, Indonesia reflects a cultural-pluralistic model of Islamization rooted in civil society, while Malaysia represents a structural-institutional model embedded within the state. This study concludes that Islamization is not merely a process of religious transmission but a historical mechanism that actively produces differentiated forms of Islam. The primary contribution lies in redefining Islamization as a multidimensional relational process that bridges the fragmentation between origin theories and the socio-political development of Islam in Southeast Asian studies.